2009
DOI: 10.1111/j.1365-2095.2008.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postprandial changes in pH along the gastrointestinal tract on the distribution of ions between the solid and fluid phases of chyme in rainbow trout

Abstract: An area of emerging importance is the role that the diet can play in alleviating the demands for ion uptake in fish living in a freshwater environment, by providing a highly concentrated supply of electrolytes. The availability of ions for uptake from the diet likely requires dissolution in the fluid phase of the chyme. However, the distribution of ions between the fluid and solid phases of chyme has not been well‐characterized in fish, and little is known about the effects of location along the gastrointestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 38 publications
5
45
1
Order By: Relevance
“…In fact, the titration of a commercial fish meal down to pH 3 (Cooper and Wilson, 2008) required 10-fold more acid than that of a natural ragworm diet (Taylor et al, 2007). It is unlikely that titration in vitro exactly duplicates the real titration that occurs as chyme is progressively digested and diluted in vivo (Bucking and Wood, 2006a;Bucking and Wood, 2008). Nevertheless, greater acid secretion with a commercial diet may reflect the greater acid-base disturbances observed in the present study when compared with studies using natural diets (Wood et al, 2007b;Taylor et al, 2007).…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…In fact, the titration of a commercial fish meal down to pH 3 (Cooper and Wilson, 2008) required 10-fold more acid than that of a natural ragworm diet (Taylor et al, 2007). It is unlikely that titration in vitro exactly duplicates the real titration that occurs as chyme is progressively digested and diluted in vivo (Bucking and Wood, 2006a;Bucking and Wood, 2008). Nevertheless, greater acid secretion with a commercial diet may reflect the greater acid-base disturbances observed in the present study when compared with studies using natural diets (Wood et al, 2007b;Taylor et al, 2007).…”
Section: Discussionmentioning
confidence: 38%
“…A K + -stimulated, H + -ATPase is responsible for the apical H + secretion, and has been identified in oxynticopeptic cells of elasmobranchs (Smolka et al, 1994) as well as those of the rainbow trout (Sugiura et al, 2006). Although there is a vigorous secretion of gastric acid at this time, the pH of the stomach fluid actually increases substantially due to the buffering action of the ingested food (Sugiura et al, 2006;Bucking and Wood, 2008). As a Cl -/HCO 3 -exchanger is believed to be responsible for the basolateral HCO 3 -export and Cl -entry, the net transfer of HCl to the stomach can lead to a reduction in plasma [Cl -] that has been correlated with an alkaline tide in toads (Busk et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not possible to measure intestinal lumen Na + levels in the loach, values measured in low salinity (2.5p.p.t. )-acclimated toadfish Opsanus beta (McDonald and Grosell, 2006) and post-prandial freshwater tilapia (Grosell, 2007) and rainbow trout (Bucking and Wood, 2006;Bucking and Wood, 2009) were within the range of the mucosal saline Na + concentrations used in this study. Thus, a favorable apical Na + electrochemical gradient would be present to drive the exchange.…”
Section: Gut Membrane Fluiditymentioning
confidence: 99%
“…Formulated or controlled feed shapes the gastrointestinal environment. Direct involvement of GI tract pH in the partitioning of bivalent ions has been shown in rainbow trout stomach (Bucking and Wood, 2009). In turn, the characteristics of GI and blood pH are influenced by diet and altered dietary electrolyte balance (Saravanan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…) and the other is characterized by continuous acid secretion and the maintenance of a low, acidic pH during fasting (Papastamatiou and Lowe, 2004;Bucking and Wood, 2009). Our results demonstrated that C. argus and S. chuatsi hold a closely neutral pH in the stomach mucosa through a long period of fasting, acidification perhaps only stimulated by the ingestion of food (Nikolopoulou et al, 2011).…”
mentioning
confidence: 99%